Rethinking mixed race - Parker, David, 1967 January 22-; Song, Miri, 1964- (Pluto Press, 2001)
Explores the complexities of mixed race in Britain and the USA.
Keywords: Multiracial people.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Ethnic Studies -- General.; Multiracial people; Interethnische Herkunft; Aufsatzsammlung; Groḃritannien; USA; Aufsatzsammlung.